THE ROLE OF THE POLICE IN DISCLOSING THE CRIMINAL ACTS OF PREDICTIVE MURDER: CASE STUDY OF BELAWAN HARBOR POLICE - Mark Sihombing, Esthon; Ekaputra, Mohammad; Trisna, Wessy (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Murder is one of the most serious crimes that not only violates criminal law provisions but also constitutes a fundamental violation of human rights, particularly the right to life that is inherent in every individual from conception and cannot be revoked by anyone except by God as the giver of life. The phenomenon of murder occurring in society, whether committed intentionally or unintentionally, is often triggered by motives of revenge or disputes between parties, thus requiring more serious and in-depth investigative handling compared to other criminal acts to thoroughly uncover cases. In the specific context of the legal jurisdiction of Belawan Port Police Resort, this normative legal research with a descriptive analytical and prospective approach examines the role of police in handling premeditated murder crimes, identifies inhibiting factors including the complexity of legal jurisdiction covering two jurisdictions (Medan City and Deli Serdang Regency), limited investigator experience, minimal operational budget, lack of facilities and infrastructure, and low public awareness in maintaining crime scenes, while analyzing efforts made by police to overcome these obstacles through preemptive activities in the form of legal counseling to the community, coordination with related activities. agencies for budget and infrastructure assistance, and capacity building for investigators through specialized training in handling criminal cases.